Seafood infusion broths as novel sources to produce organic acids using selected lactic acid bacteria strains - Ozogul, Fatih; Ozcelik, Sezen; Ozogul, Yesim; Yilmaz, Mustafa Tahsin (ELSEVIER, 2021)
In this study, LAB strains were used to produce organic acids from various seafood infusion broths (European eel, European squid, shrimp and octopus) and M17 broth. There were significant differences (P < 0.05) between the organic acid amounts produced by LAB strains propagated in seafood infusion and M17 broths. Succinic acid was produced at the highest amounts. Maximum amounts (1747.7 and 872.1 mg/L) of formic and acetic acids were produced by L. acidophilus in octopus infusion broth, while maximum amounts (9852.8 and 3999.6 mg/L) of propionic and butyric acids were formed by S. thermophilus in shrimp infusion broth. It was observed that European eel, shrimp and octopus infusion broths exhibited a greater performance than M17 broth in terms of production of formic, lactic, acetic, propionic and butyric acids. All these results showed that LAB strains had a great ability to form the organic acids in the developed seafood infusion broths. This is a striking result given that the recent implementation of new technologies has divulged the importance of lactic acid bacteria that can find a wide application area in bio-manufacturing, food, agriculture, livestock and medical health industries.
Keywords: Organic acid; Seafood infusion broth; Lactic acid bacteria; HPLC; M17 broth; BIO-BASED PRODUCTION; SUCCINIC ACID; FERMENTATION; OPTIMIZATION; CHEMICALS; MEAT; Food Science & Technology